A Kampo formula, saikokaryukotsuboreito, improves serum testosterone levels of castrated mice and its possible mechanism. (March 2013) - Michihara, Seiwa; Shin, Noriyuki; Watanabe, Shimpei; Morimoto, Yasuo; Okubo, Toshiki; Norimoto, Hisayoshi
Abstract The term "late-onset hypogonadism (LOH)" is recommended to express the symptoms in middle-aged males with decreased testosterone. Although androgen replacement therapy (ART) might be an effective way to manage LOH, the risk of testosterone supplementation in elderly men is still concerned. On the other hand, to avoid adverse effects of ART, Kampo medicine (traditional Chinese–Japanese medicine) is often a first choice to treat LOH in Japan. However, their pharmacological studies are few. In this study, castrated mice was used as an LOH animal model for examining the pharmacological effects of a Kampo formula, saikokaryukotsuboreito (shortly SKRBT) on serum testosterone levels and seminal vesicles weights. Furthermore, an attempt to elucidate its pharmacological mechanism, inhibition of SKRBT and its components against aromatase were also examined with the enzyme-based assay. As a result, SKRBT improved significantly both the decline of serum testosterone levels and decrease of seminal vesicles weight of castrated mice at a dose of 125 mg/kg with a non dose-dependent manner. SKRBT and two components Scutellariae radix and Rhei rhizoma exhibited inhibitory activities with the IC50 values of 145, 29.2 and 29.7 µg/ml, respectively. These results suggested that the aromatase inhibitory activity of SKRBT may contribute, to a different extent, to the improvement of serum testosterone levels.